PROCEDURES FOR ESTABLISHING LAND BOUNDARIES IN THE COMMUNITY OF EAST BAKONGAN DISTRICT BASED ON CONCEPT OF 'UQAR MAL - Elida Gusmira; Saifuddin Sa'dan; Faisal Fauzan (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2018)
Abstract: The problem concerning the land boundaries is the designation of land boundaries set by the landowner. Before the measurement of the land, the landowner must install pegs at each vertex of the boundary to be measured by the party determined. The measurement should be witnessed by the head of the village, the village officials, and the parties who are bordered with the land. The research problem was that the determination of boundary markers does not include the head of the village and the related parties bordered with the land. Instead, the landowner establishes the boundary markers by himself. The results indicated that all unresolved land boundary issues were due to the unwillingness of the community to report to the authorities. The procedure of land measurement should be conducted by placing pegs in advance on the land boundaries to be measured by the responsible party with several witnesses, and between the two the bordering parties, accompanied by the head of the village. This procedure controls the land boundary issues so it will cause no harm for the owner and other parties. Abstrak: Permasalahan penetapan batas tanah merupakan penunjukan batas-batas bidang tanah yang ditetapkan oleh pribadi (pemilik tanah itu sendiri) sebelum dilaksanakan pengukuran atas bidang tanah pemilik tanah harus memasang patok pada setiap titik-titik sudut batas yang akan diukur oleh pihak yang telah ditentukan. Disaksikan oleh kepala desa, aparatur-aparatur desa, dan para pihak yang berbatasan tanah. Permasalahan yang terdapat dalam penelitian bahwa penetapan tanda batas tidak diikutserta oleh kepala desa dan para pihak yang berbatasan tanah, akan tetapi pihak pribadi tanah mendirikan tanda batas dengan sendirinya. Hasil dari penelitian menunjukkan bahwa segala bentuk permasalahan batas tanah ada yang belum terselesaikan dikarenakan masyarakat tidak ingin melaporkan kepada pihak berwajib. Prosedur penetapan pengukuran tanah seharusnya dengan cara memberi patok terlebih dahulu pada batas tanah yang akan diukur oleh pihak penanggung jawab dengan beberapa saksi dan antara kedua belah pihak yang berbatasan disertai kepala desa. Hal ini untuk pengendalian permasalahan batas tanah agar tidak terjadi hal-hal yang tidak merugikan diri sendiri dan pihak lain. Kata Kunci : Tatacara, Penetapan Batas Tanah, Konsep Mal ‘Uqar.